1975
DOI: 10.2134/jeq1975.00472425000400030027x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate, Phosphorus, and Sulfate in Subsurface Drainage Water

Abstract: Measurements made over a 4‐year study of flow and NO3‐N, PO4‐P, total P, and SO4‐S content of subsurface drainage water from tile‐drained cropland indicate that annual nutrient losses are highly variable. Annual losses of phosphorus, SO4‐S, and NO3‐N ranged from 0 to 0.04, 0 to 32, and 0 to 93 kg/ha, respectively, being very dependent on the amount of water lost. Because of low concentrations of phosphorus, losses with subsurface drainage water were insignificant when compared with losses associated with surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
109
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 0 publications
5
109
0
Order By: Relevance
“…Until recent years, the focus of drainage research and development was to improve its efficiency and increase crop yields and profits. Research beginning in the 1970s (e.g., Baker et al 1975;Gambrell et al 1975) showed that agricultural drainage has significant impacts on surface water quality. Subsurface drainage reduces surface runoff, sediment losses, and the movement of contaminants attached to the sediment into surface waters.…”
mentioning
confidence: 99%
“…Until recent years, the focus of drainage research and development was to improve its efficiency and increase crop yields and profits. Research beginning in the 1970s (e.g., Baker et al 1975;Gambrell et al 1975) showed that agricultural drainage has significant impacts on surface water quality. Subsurface drainage reduces surface runoff, sediment losses, and the movement of contaminants attached to the sediment into surface waters.…”
mentioning
confidence: 99%
“…Subsurface drainage in combination with intensively cropped agricultural lands may lead to high nitrate mass loadings in surface waters with many authors documenting high nitrate concentrations and loadings in midwestern drainage (Baker et al, 1975;Kalita et al, 2006;Jaynes et al, 2008). These agricultural sources of nitrogen in the Upper Mississippi River Basin are thought to be a significant contributor to the hypoxic zone in the Gulf of Mexico, and the U.S. EPA Science Advisory Board has called for loading reductions of 45% of riverine total nitrogen flux in order to decrease the size of the hypoxic zone (USEPA , 2007).…”
mentioning
confidence: 99%
“…This article is available at Iowa State University Digital Repository: http://lib.dr.iastate.edu/abe_eng_pubs/483 A gricultural chemicals in surface water bodies and groundwater aquifers are recognized as major contributors to the water quality problem in many areas of the United States, especially the Midwest. One of the major pollutants is nitrate-nitrogen (NO 3 -N) which is very susceptible to leaching to groundwater systems, and possibly causing environmental, economic, and energy conservation concerns (Baker et al, 1975;Galinato, 1987;Kanwar et al, 1988). Researchers have reported excess NO 3 -N concentrations in drainage waters and groundwater (Baker and Johnson, 1981;Hallberg et al, 1986;Kladivko et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major pollutants is nitrate-nitrogen (NO 3 -N) which is very susceptible to leaching to groundwater systems, and possibly causing environmental, economic, and energy conservation concerns (Baker et al, 1975;Galinato, 1987;Kanwar et al, 1988). Researchers have reported excess NO 3 -N concentrations in drainage waters and groundwater (Baker and Johnson, 1981;Hallberg et al, 1986;Kladivko et al, 1991).…”
mentioning
confidence: 99%